(untitled) (Medical Forum Monthly, 2023)
Objective: To evaluate and compare satisfaction of medical students with their teacher’s teaching, during on line versus face to face academic sessions. Study Design: Cross sectional, comparative study Place and Duration of Study: This study was conducted at the University College of Medicine (UCM), The University of Lahore from March 2020 to December 2021. Materials and Methods: In this study, we included all enrolled medical students and teachers from first to final academic year. Data was collected at two points, first at the end of 2020, when all the studies were mostly on line due to COVID-19 lock down. Second data collection point was at the end of 2021, when almost all studies were face to face due to controlled COVID-19 situation in Pakistan. After taking consent, students were asked about their satisfaction with teachings first during on line and second about same teachers during face to face academic sessions. Used questionnaires was developed based on Higher Education Commission Pakistan guide lines. Both questionnaires have ten closed and one open ended questions. After collection, data was analyzed using mean, median and t-test considering P<0/05 level of significance. Results: Our study found, medical students were more satisfied with teaching of their teachers during face to face, academic session of 2021as compared to on line session of 2020.When compared, we found significant difference in satisfaction of medical students with same teacher’s teaching during on line, in 2020 (4.11±0.21) versus face to face in 2021 session (4.26+ 0.23). This result is highly significant with p value P< 0.00.Year wise medical year comparison revealed highly significant results in first, third and final year medical studies, while insignificant in fourth and first year of medical studies. The mean of satisfaction of students with their teacher’s teaching during on line session of 2020 in first, second, third, fourth and final year of medical studies were found (4.28±0.17), (4.07±0.23), (4.06±0.15), (4.18±0.23) and (4.00±0.18) respectively. The mean of satisfaction of students with their teacher’s teaching during face to face session in 2021 in first, second, third, fourth and final year of medical studies were found (4.31±0.32),(4.26±0.17), (4.23±0.16),(4.29±0.30)and (4.23±0.19) respectively. Conclusion: It is concluded that medical students are found more satisfied with face to face as compare to on line teaching of same teachers.